MENGAPA KONFLIK BERULANG TERJADI DI KOTA AMBON? TINJAUAN DEMOGRAFI DAN KEAMANAN ATAS KONFLIK HORIZONTAL PERKOTAAN - Poltak Partogi Nainggolan (Jurnal Politica, 2012)
Riots in Ambon often recurred within short intervals since the last 2001 protracted horizontal conflict. Many attempted to partially analyze these phenomena by focusing only the trigger of the riots such as individual crimes and bad police behavior, ignoring to discuss the cause of the conflicts from their roots, namely the demographic factors, such as population growth and its density and interactions. Early data collection of this research was conducted in Jakarta and local libraries and central statistic bureau. Its analysis uses a qualitative method, and its research report was made based on an analytical-descriptive direction. This research reveals that the current structure of Ambonese population, segregation, and development malfunction create a sufficient condition for re-emergence of new social conflict in the city. The cause of these are the absence of the city government’s interventions with its policies in controlling and restructuring the population growth and eliminating both the long-existed segregation and the development malfunction. Applying a combination of security studies and urban sociology approaches becomes relevance, and also, fruitful in this research.